Challenges and Opportunities to Well Education - Sari, Fitria (The Future of Education Journal, 2024)
High-quality human resources and the progress of a country heavily rely on education. In Indonesia, the education sector faces significant challenges that hinder progress, such as insufficient funding, disparities between urban and rural education, and uneven quality across various institutions. These challenges often result in disparities in access and learning opportunities for students in different regions. Nonetheless, Indonesia also holds substantial potential to improve and enhance its educational quality. A key opportunity lies in leveraging rapidly advancing technology and information, which can help bridge educational gaps and provide better resources for students and teachers. The aim of this paper is to delve into the difficulties faced in the education sector and identify opportunities to improve the quality of education in Indonesia comprehensively. By understanding these challenges and utilizing existing potential, it is hoped that a more inclusive and high-quality education system can be created to support national progress